Pengaruh Servant Leadership dan Self-Efficacy terhadap Psychological Well-being yang dimediasi Life Satisfaction pada Karyawan Mixue di Tangerang - Tsabitah, Dinah Amira; Chairunisah, Nabillah; Emilisa, Netania; Ananditha, Kania Reskia (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the effect of Servant Leadership and Self-Efficacy on Psychological Well-being mediated by Life Satisfaction. The approach used is quantitative and uses a purposive sampling technique. The research was conducted by taking a sample of Mixue employees in Tangerang in the form of a questionnaire containing questions related to the variables studied with a total of 105 respondents. The test results on the available data show that Servant Leadership has a positive influence on both Life Satisfaction and Psychological Well-being. However, Self-Efficacy is known to have no positive or significant effect either on Life Satisfaction or on Psychological Well-being.